Lipoaspiration and Processing to Create Microfragmented Adipose Tissue - Cally McGee MD; Michael R. Baria MD, MBA; Corey Gatewood BA; Maneesh Tiwari MD; W. Kelton Vasileff MD; Chad Lavender MD (SAGE Publishing, 2022)
Background: Orthobiologics are increasingly used to treat musculoskeletal (MSK) conditions. Adipose may be a useful source of autologous cells for orthobiologic interventions. The lipoaspiration and processing techniques necessary to obtain these cells are not traditionally taught in most orthopedic training programs. Therefore, the goal of this video is to review the technique for adipose harvest and preparation to create microfragmented adipose tissue (MFAT). Indications: Currently, all MFAT applications are off-label. In practice, this is most commonly used for osteoarthritis and tendon disease. Technique Description: After local anesthesia is administered, a 17-gauge trochar is inserted into the subcutaneous adipose, and tumescent solution is injected. After a 5-minute waiting period, a separate 17-gauge harvest trochar is attached to the Autopose double-syringe (Arthrex; Naples, Florida) and is inserted into the subcutaneous adipose. Lipoaspiration is performed by moving the harvest device back and forth in a fan-like pattern. After 20 mL of lipoaspirate has been harvested from the first site, the lipoaspiration process is repeated on the contralateral side. After 40 mL of lipoaspirate has been harvested, the device is removed and decanted for 3 to 5 minutes. Then, 10 mL of sterile saline solution is injected into the device using the Luer lock attachment. This rinse process is repeated a second time. Once the excess fluid has been removed, the device is capped, and the outer syringe is slowly pushed down to move the tissue through the resizing filter. The inner syringe is removed and contains the final MFAT product. Discussion/Conclusion: Lipoaspirate is a simple technique that can be performed in the clinic or operating room to create MFAT. This provides a unique population of autologous cells that may be beneficial for treating MSK pathology.